PENGARUH PENERAPAN METODE ROLE PLAYING TERHADAP HASIL BELAJAR IPS PESERTA DIDIK KELAS IX - Azizah, Afidatul; Salam, Rudi (Universitas Negeri Semarang, 2023)
Learning must be able to provide provisions for students to think critically, logically, analytically, systematically and creatively. To provide provisions for students, social studies learning is needed that is innovative, interesting and fun for students so that social studies subjects are not considered as bad subjects. rote and boring which will impact students' interest and learning outcomes in social science subjects. Learning outcomes are changes in behavior that occur after following the teaching and learning process in accordance with educational objectives. Based on observations, social studies learning at SMP Ma'arif NU 03 Jatinegara Tegal Regency still uses the lecture and question and answer method, occasionally using PowerPoint. Even though there is a variety of students, there are still many who are passive and bored in monotonous learning so that learning outcomes in social studies learning are still relatively low. Based on the results of research and data analysis, there is an influence of the application of the role playing method on the learning outcomes of class IX students in social studies subjects on natural conditions of countries in the world. Pembelajaran harus mampu memberikan bekal kepada peserta didik untuk berfikir kritis, logis, analisis, sistematis, dan kreatif, untuk memberikan bekal kepada peserta didik maka diperlukan pembelajaran IPS yang inovatif, menarik dan menyenangkan bagi peserta didik agar mata pelajaran IPS tidak dianggap sebagai mata pelajaran yang hafalan dan membosankan yang akan berimbas pada minat dan hasil belajar peserta didik pada mata pelajaran ilmu pengetahuan sosial. Hasil belajar merupakan perubahan perilaku yang terjadi setelah mengikuti proses belajar mengajar sesuai dengan tujuan pendidikan. Berdasarkan hasil observasi bahwa pembelajaran IPS di SMP Ma’arif NU 03 Jatinegara Kabupaten Tegal masih menggunakan metode ceramah dan tanya jawab, sesekali menggunakan powerpoint. Meskipun bervariasi peserta didik masih banyak yang pasif dan bosan dalam pembelajaran yang monoton sehingga hasil belajar dalam pembelajaran IPS masih tergolong rendah. Berdasarkan hasil penelitian dan analisis data terdapat pengaruh penerapan metode role playing terhadap hasil belajar peserta didik kelas IX pada mata pelajaran IPS materi kondisi alam negara-negara di dunia.